The Application of Thera-band on Non-weight Bearing Leg Influence Hip Abductor Activities During Pelvic Drop Exercise in Patients With Gluteus Medius Weakness - Su-hwan Cha; Seok-hyun Kim; Seung-min Baik; Heon-seock Cynn (Korean Research Society of Physical Therapy, 2023)
Background: The weakness of the gluteus medius (GM) is associated with various musculoskeletal disorders. The increasing GM activity without synergistic dominance should be considered when prescribing pelvic drop exercise (PD). Isometric hip extension or flexion of the non-weight bearing leg using thera-band at the ankle during PD may influence hip abductor activities. Objects: To determine how isometric hip extension or flexion of the non-weight bearing leg using thera-band at the ankle during PD influences the activities of three subdivisions of GM (anterior, GMa; middle, GMm; posterior, GMp), tensor fasciae latae (TFL), contralateral quadratus lumborum (QL), and GMp/TFL, GMm/QL activity ratios in patients with GM weakness. Methods: Twenty-three patients with GM weakness were recruited. Three types of PD were performed: PD, PD with an isometric hip extension of the non-weight bearing leg (PDE), and PD with an isometric hip flexion of the non-weight bearing leg (PDF). Surface electromyography (SEMG) was used to measure hip abductor activities. One-way repeated-measures analysis of variance was used to assess the statistical significance of muscle activities and muscle activity ratios. Results: GMa, GMm, and GMp activities were significantly greater during PDF than during PD and PDE (p < 0.001, p = 0.001; p = 0.001, p = 0.005; p = 0.004, p = 0.004; respectively). TFL activity was significantly greater during PDE than during PD and PDF (p < 0.001, p < 0.001, respectively). QL activity was significantly greater during PDF than during PD (p = 0.003). GMp/TFL activity ratio was significantly lower during PDE than during PD and PDF (p = 0.001, p = 0.001, respectively). There were no significant differences in the GMm/QL activity ratio. Conclusion: PDF may be an effective exercise to increase the activities of all three GM subdivisions while minimizing the TFL activity in patients with GM weakness.